1990
DOI: 10.1007/bf01731128
|View full text |Cite
|
Sign up to set email alerts
|

Unequal crossing over and heterochromatin exchange in the X-Y bivalents of the deer mouse,Peromyscus beatae

Abstract: Differences in length of the heterochromatic short arms of the X and Y chromosomes in individuals of Peromyscus beatae are hypothesized to result from unequal crossing over. To test this hypothesis, we examined patterns of synapsis, chiasma formation, and segregation for male P. beatae which were either heterozygous or homozygous for the amount of short-arm sex heterochromatin. Synaptonemal complex analysis demonstrated that mitotic differences in heterochromatic short-arm lengths between the X and Y chromosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…eliurus (FURTADO 1981) and in 0. nigripes (ALMEIDA and YONENAGA-YASSUDA 1991). Recently, SunMAN and GREENBAUM (1990) demonstrated that unequal crossing overs between the heterochromatic short arms of the X and Y chromosomes are responsible for the production and propagation of polymorphisms in the sexual pair of Peromyscus beatae.…”
Section: Oryzomys Subflavusmentioning
confidence: 99%
“…eliurus (FURTADO 1981) and in 0. nigripes (ALMEIDA and YONENAGA-YASSUDA 1991). Recently, SunMAN and GREENBAUM (1990) demonstrated that unequal crossing overs between the heterochromatic short arms of the X and Y chromosomes are responsible for the production and propagation of polymorphisms in the sexual pair of Peromyscus beatae.…”
Section: Oryzomys Subflavusmentioning
confidence: 99%
“…In Peromyscus, the heterochromatic short arm ofthe X chromosome and a corresponding arm of the heterochromatic Y chromosome comprise the pseudoautosomal region (Hale and Greenbaum, 1986;Sudman and Greenbaum, 1990;Hale et al, 1991;Fig. I).…”
Section: V Notes and Commentsmentioning
confidence: 99%
“…Because genetic and molecular markers are not available for the pseudoautosomal region of the deer mouse, the possibility that X-Y recombination is limited to a very small segment within this region cannot be summarily excluded. The random distribution of chiasmata observed within the heterochromatic pseudoautosomal segments in deer mice (Hale and Greenbaum, 1986;Sudman and Greenbaum, 1990;Hale et al, 1991) and other rodent species (Murer-Orlando and Richer, 1983;Schmid et al, 1987;Latos-Bielenska and Vogel, 1992) could simply reflect progressive terminalization from a small recombinational hotspot located near the X and Y centromeres. However, cytogenetic data from populations of P. beatae exhibiting quantitative variation for the amount of pseudoautosomal heterochromatin clearly indicate that meiotic crossing over occurs throughout the pseudoautosomal region (Sudman and Greenbaum, 1990).…”
Section: V Notes and Commentsmentioning
confidence: 99%
See 2 more Smart Citations